Effects of Keratinocyte-Derived Cytokine (CXCL-1) on the Development of Theiler's Virus-Induced Demyelinating Disease - Kang, Min H.; Jin, Young H.; Kim, Byung S. (Frontiers in Cellular and Infection Microbiology, 2018)
CXCL-1, also called keratinocyte-derived cytokine (KC), is a predominant chemokine produced in glial cells upon infection with Theiler’s murine encephalomyelitis (TMEV). In this study, we assessed the role of KC in the development of TMEV-induced demyelinating disease by utilizing polyclonal anti-KC antibodies as well as KC-expressing recombinant TMEV. Our results indicate that the level of KC produced after infection with TMEV or stimulation with various TLRs is significantly higher in various cells from susceptible SJL mice compared to those in cells from resistant B6 mice. SJL mice treated with rabbit anti-KC antibodies displayed accelerated development of TMEV-induced demyelinating disease, elevated viral loads in the CNS and decreased antiviral T cell responses. In addition, infection of susceptible SJL mice with recombinant KC-TMEV produced biologically active KC, which resulted in the accelerated pathogenesis of demyelinating disease and elevated T cell responses to viral antigens compared to mice infected with control recombinant HEL-TMEV. These results strongly suggest that both the lack of KC during TMEV infection and the excessive presence of the chemokine promote the pathogenesis of demyelinating disease. Therefore, a balance in the level of KC during TMEV infection appears to be critically important in controlling the pathogenesis of demyelinating disease.